Evaluation of some insects as potential feed ingredients for ruminants: chemical composition, in vitro rumen fermentation and methane emissions - Jayanegara, A.; Yantina, N.; Novandri, B.; Laconi, E. B.; Nahrowi, N.; Ridla, M. (Diponegoro University, 2017)
This experiment was aimed to evaluate chemical composition, in vitro rumen fermentation, digestibility and methane emissions of some insects, i.e. Jamaican field cricket (JFC), mealworm (MW) and black soldier fly larvae age 1 and 2 weeks (BSF1 and BSF2). Insect samples were oven-dried at 60oC for 24 h, and ground to pass a 1 mm sieve. The ground samples were used subsequently for chemical composition determination and in vitro rumen fermentation test. Incubation was carried out in a water bath maintained at 39 ºC for 48 h in three replicates. Results revealed that all insect meals contained high crude protein, i.e. above 40% DM. Proportions of neutral detergent insoluble CP (NDICP) and neutral detergent insoluble CP (ADICP) were high in the insect meals than that of soybean meal (SBM), and these were particularly very high in BSF2. All insect meals had lower IVDMD and IVOMD than that of SBM (P<0.05). All insect meals had lower methane emissions as compared to SBM at 12, 24 and 48 h (P<0.05). It can be concluded that insect meals are potential protein supplements and have low methane emissions in vitro. However, their digestibility is rather low and may limit their utilization.